Pengaruh Gaya Kepemimpinan Transformasional dan Komitmen Organisasi terhadap Kinerja Karyawan Salon Andesya Studio Bukittinggi - Amelia, Rizki Putri; Reflianto, Reflianto; Astuti, Murni; Saputra, Indra (Lembaga Yasin AlSys, 2025)
This study aims to examine the influence of transformational leadership style and organizational commitment on employee performance at Andesya Studio Salon in Bukittinggi. A quantitative approach was employed using a causal analysis method, where the independent variables were transformational leadership style and organizational commitment, and the dependent variable was employee performance. The research sample consisted of 32 employees selected through a total sampling technique. Data were collected using a questionnaire that had been tested for validity using Pearson correlation and for reliability using Cronbach’s Alpha coefficient. Data were analyzed using multiple linear regression, with t-tests to assess the partial effect of each independent variable on the dependent variable, and an F-test to evaluate their simultaneous effect. The findings are expected to provide empirical evidence on the contribution of transformational leadership style and organizational commitment to improving employee performance. The implications of this study offer a more comprehensive understanding of the strategic role of leadership and organizational commitment in optimizing employee performance within the service sector.